INFLUENCE OF SEED PRE-TREATMENT AND TEMPERATURES DURING GERMINATION OF FOUR SEED LOTS OF FESTULOLIUM - Stanisavljević, Rade (Journal on Processing and Energy in Agriculture, 2022)
A species called Festulolium was created in the middle of the last century by crossing two genuses: Lolium and Festuca. This was followed by a period of research on Festulolium from the aspect of genetics and breeding, seed production, cultivation, technology and use. We conducted various pre-treatment impact studies on Festulolium seeds: i) cooling at 5-7 oC for 3 days, ii) application of KNO3 on seed germination medium, and the third pre-treatment was control, without pre-treatment (iii). After pre-treatment (i, ii, iii), seed germination have examined at the following temperature regimes (provided by the seed quality regulations): 20 oC (dark); alternately 20oC/ 30oC (light /dark); and 30 oC (dark). The tests were performed on four seed lots of the variety Peron, in four replicates. The germination temperature of 30 oC reduced germination and increased dead seed and abnormal germination in all pre-treatments. The variant without the application of pre-treatment had a significantly lower overall germination in the assessment of Festulolium seed quality. Seed lots showed a high influence on the Festulolium seed quality.